Causes of death among undocumented migrants in Sweden, 1997-2010 - Anna Wahlberg; Carina Källestål; AnnaCarin Lundgren; Birgitta Essén (Taylor & Francis Group, 2014)
Background: Undocumented migrants are one of the most vulnerable groups in Swedish society, where they generally suffer from poor health and limited health care access. Due to their irregular status, such migrants are an under-researched group and are not included in the country's Cause of Death Register (CDR). Objective: To determine the causes of death among undocumented migrants in Sweden and to ascertain whether there are patterns in causes of death that differ between residents and undocumented migrants. Design: This is a cross-sectional study of death certificates issued from 1997 to 2010 but never included in the CDR from which we established our study sample of undocumented migrants. As age adjustments could not be performed due to lack of data, comparisons between residents and undocumented migrants were made at specific age intervals, based on the study sample's mean age at death±a half standard deviation. Results: Out of 7,925 individuals surveyed, 860 were classified as likely to have been undocumented migrants. External causes (49.8%) were the most frequent cause of death, followed by circulatory system diseases, and then neoplasms. Undocumented migrants had a statistically significant increased risk of dying from external causes (odds ratio [OR] 3.57, 95% confidence interval [CI]: 2.83-4.52) and circulatory system diseases (OR 2.20, 95% CI: 1.73-2.82) compared to residents, and a lower risk of dying from neoplasms (OR 0.07, 95% CI: 0.04-0.14). Conclusions: We believe our study is the first to determine national figures on causes of death of undocumented migrants. We found inequity in health as substantial differences in causes of death between undocumented migrants and residents were seen. Legal ambiguities regarding health care provision must be addressed if equity in health is to be achieved in a country otherwise known for its universal health coverage.